Position statement on interferon-γ release immunoassays in the detection of latent tuberculosis infection, October 2007 - National Tuberculosis Advisory Committee (Communicable Diseases Intelligence, 2007)
This document endorsed by the National Tuberculosis Advisory Committee is a general guide to appropriate practice, to be followed in the detection of latent tuberculosis infection.